2013
DOI: 10.3906/sag-1208-60
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial dilatation in undetermined group according to TOAST classification: echocardiographic assessment of stroke patients

Abstract: Th is paper presents the author's integrated regional studies during the last decade. Th e main purpose is to present an overall understanding of the geological structure, sedimentary basins and hydrocarbon systems of the whole Western Black Sea Zone (WBSZ). Th is study is based on original data from boreholes, seismic and gravity-magnetic surveys and hydrocarbon accumulations.Many geophysical borehole data obtained for WBSZ during the last 3-4 decades were interpreted mostly at a national level using diff ere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…In our study, we detected significant involvement of AF in cardioembolic strokes. In our country Takoğlu, et al observed also the same result in the undetermined LAD group (p<0.038) [32]. …”
Section: Discussionsupporting
confidence: 81%
“…In our study, we detected significant involvement of AF in cardioembolic strokes. In our country Takoğlu, et al observed also the same result in the undetermined LAD group (p<0.038) [32]. …”
Section: Discussionsupporting
confidence: 81%
“…Second, compared to other types of ischemic stroke, CE has a more abrupt onset with more severe conditions and a higher NIHSS score [ 16 , 17 ]. Third, a number of recent studies have confirmed that left atrial enlargement is correlated with stroke and can increase the risk of stroke [ 18 20 ], especially the risk of CE [ 21 ].As an important etiological factor in stroke of undetermined etiology [ 22 ]and an independent risk factor for CE and the recurrence of cryptogenic stroke [ 23 ],left atrial enlargement is associated with the stroke severity [ 24 ].Additionally, left atrial enlargement may lead to local thrombosis [ 25 ]. Jaroch et al found that a left atrial diameter greater than 51 mm was an independent risk factor for predicting thrombus in the left atrial appendage [ 26 ].…”
Section: Discussionmentioning
confidence: 99%